Transmission of ceftazidime-avibactam-resistant Escherichia coli among pets, veterinarians and animal hospital environment - Hegen Dai; Dongyan Shao; Yu Song; Qi An; Zhenbiao Zhang; Haixia Zhang; Siyu Chen; Congming Wu; Jianzhong Shen; Yanli Lyu; Yang Wang; Shizhen Ma; et al. (Elsevier, 2024)
Ceftazidime-avibactam (CZA) is a recently approved combination synthetic β-lactamase inhibitor used in human clinical medicine. Cases of CZA resistance in humans have already been reported, but limited research has investigated CZA resistance in pets. This study explored the prevalence and transmission of CZA-resistant Escherichia coli (CZAREC) among pets, their owners, veterinarians, and the environment in animal hospitals. A total of 5,419 clinical samples were collected from dogs and cats, along with samples from the environment (n = 5,843), veterinarians (n = 557), and pet owners (n = 368) in animal hospitals. From these samples, 760 Escherichia coli (E. coli) isolates were obtained, out of which 60 were identified as CZAREC. These included 34 isolates from the environment (9.14 %, n = 372), three from veterinarians (8.11 %, n = 37), and 23 from animals (6.82 %, n = 337). No CZAREC isolates were found in pet owners. The predominant sequence types of CZARECs were ST156 (n = 20), ST410 (n = 19) and ST101 (n = 7). Bayesian analysis revealed six clusters comprising 47 isolates from the hospital environment, pets, and veterinaries, displaying genetic relatedness of less than 100 core genome single nucleotide polymorphisms (cgSNPs) between any two isolates in each cluster. Some CZAREC isolates with high genetic similarity persisted in the same animal hospital for four to six months. Moreover, discriminant analysis of principal components indicated that most isolates from different hosts shared a genetic source in the human/dog/cat merged cluster. Overall, evidence of CZARECs transmission was found among pets, the environment, and veterinarians in animal hospitals. The findings emphasize the importance of monitoring CZARECs in the veterinary clinical setting to ensure the health of both pets and humans.